Experimental and simulation study on the effect of geometrical and flow parameters for combined-hole film cooling - Hassan, Haswira (2016)
Film cooling method was applied to the turbine blades to provide thermal protection from high turbine inlet temperatures in modern gas turbines. Recent literature discovers that combining two cylindrical holes of film cooling is one of the ways to further enhance the film cooling performances. In the present study, a batch of simulations and experiments involving two cylindrical holes with opposite compound angle were carried out and this two cylindrical hole also known as combined-hole film cooling. The main objective of this study is to determine the influence of different blowing ratio, M with a combination of different lateral distance between cooling holes (PoD), a streamwise distance between cooling holes (LoD) and compound angle of cooling hole (1/2) on the film cooling performance. The simulation of the present study had been carried out by using Computational Fluid Dynamic (CFD) with application of Shear Stress Transport (SST) turbulence model analysis from ANSYS CFX. Meanwhile, the experimental approach makes used of open end wind tunnel and the temperature distributions were measured by using infrared thermography camera. The purpose of the experimental approach in the present study is to validate three cases from all cases considered in the simulation approach. As the results shown, the lateral coverage was observed to be increased as PoD and 1/2 increased due to the interaction between two cooling air ejected from both cooling holes. Meanwhile, film cooling performance insignificantly changed when different LoD was applied. As the conclusion, a combination of the different geometrical parameters with various flow parameters produced a pattern of results. Therefore, the best configuration has been determined based on the average area of film cooling effectiveness. For M = 0.5, PoD = 1.0, LoD = 2.5 and 1 / 2 = -45o /+45o case is the most effective configuration. In the case of M = 1.0 and M = 1.5, PoD = 0.0, LoD = 3.5, 1 / 2 = -45o /+45o and PoD = 0.0, LoD = 2.5, 1 / 2 = -45o /+30o are the best configurations based on the overall performance of film cooling.